2014
DOI: 10.7475/kjan.2014.26.1.46
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Gender Role Conflict and Job Satisfaction upon Organizational Commitment in Male Nurses

Abstract: Purpose: This study was to investigate the influence of male nurses' gender role conflict and job satisfaction on their organizational commitment. Methods: Data were collected through a mixed method design using structured questionnaires (N=162) and a sequential qualitative interviews (N=8) from 2nd October, 2012 to 7th February, 2013. Data analysis included t-test, ANOVA, regression with SPSS/WIN 19.0 program and a qualitative thematic analysis. Results: Factors affecting participants' organizational commitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
10
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
6
10
1
2
Order By: Relevance
“…The first theme cluster was "compliance with the workplace culture", which consisted of "living in a vertical ward culture" and "paying your dues". The female-centric, conservative, and hierarchical organizational structure observed in this study is consistent with that reported in some past research [25] and Korea's clinical culture. We posit that a free communication system, in which male and female nurses within a nursing organization can cooperate and not be hindered by a strict vertical relationship, should be promoted within clinical settings.…”
Section: Discussionsupporting
confidence: 91%
“…The first theme cluster was "compliance with the workplace culture", which consisted of "living in a vertical ward culture" and "paying your dues". The female-centric, conservative, and hierarchical organizational structure observed in this study is consistent with that reported in some past research [25] and Korea's clinical culture. We posit that a free communication system, in which male and female nurses within a nursing organization can cooperate and not be hindered by a strict vertical relationship, should be promoted within clinical settings.…”
Section: Discussionsupporting
confidence: 91%
“…수, 간호사는 여성 직업이라는 고정관념 등으로 간호직을 떠나 는 적지 않다 [8,9]. 여러 연구 [1,5,10] ․ Decide to become a person who is helpful to others ․ Make an effort to change and counteract in different ways depending on people ․ Try to greet difficult people first ․ Change mind that adaptation involves changing myself ․ Counsel with an administrator, requesting to move to a special department ․ Introduce myself to patients first ․ Explain to rejected patient and obtain consent ․ Receive help from female nurses in work if needed ․ Make effort to behave sensibly when dining together…”
mentioning
confidence: 99%
“…Given this, fostering appropriate empathy in the growing number of male nurses at LTC hospitals appears to be an increasingly important concern. Gender differences should be taken into account when developing and implementing programs on building empathy, since male and female nurses may possess different degrees and perception of this capacity [26].…”
Section: Discussionmentioning
confidence: 99%